A new spray-type adhesion barrier (AdSpray) improves condition for surgical treatment in the reversal of Hartmann procedure: A case report. Issue 48 (3rd December 2021) - Osumi, Wataru; Yamamoto, Masashi; Masubuchi, Shinsuke; Hamamoto, Hiroki; Ishii, Masatsugu; Izuhara, Keisuke; Taniguchi, Kohei; Kuramoto, Toru; Suzuki, Yusuke; Tanaka, Keitaro; Okuda, Junji; Uchiyama, Kazuhisa
Abstract: Rationale: Hartmann procedure (HP) often causes severe postoperative adhesions in the pelvic space; therefore, the reversal of Hartmann procedure (RHP) is a challenging surgery. A new spray-type antiadhesion agent, AdSpray, has been reported to be useful in three-dimensional fields such as the liver. However, there are no reports of its use in HP. We present a case of a male patient with rectal cancer who underwent laparoscopic HP with AdSpray to prevent postoperative adhesions. Patient concerns: A 52-year-old man presented with melena and constipation. Diagnosis: Colonoscopy revealed an almost obstructive type II tumor at the rectosigmoid colon, and histopathological examination revealed moderately differentiated adenocarcinoma. Enhanced abdominal computed tomography revealed slightly enlarged regional lymph nodes but no ascites around the tumor, and there was no metastasis to the liver or lungs. Therefore, we diagnosed clinical stage T4aN1bM0 rectosigmoid colon cancer. Intraoperatively, a metastatic tumor of the liver surface and a high degree of valve retention in the oral colon were identified. Interventions: After performing laparoscopic HP with AdSpray, we scheduled a laparoscopic RHP with staged hepatic surgery for synchronous liver metastasis from colorectal cancer 1 month later. Outcomes: No postoperative inflammatory adhesions were observed in the pelvis or around the rectal stump, allowing us to perform RHP by a single-incision laparoscopic surgery from the stoma site without any problem. The operation time for RHP was 80 minutes; the patient was in good general condition after the operation, and he was discharged on postoperative day 7. Lessons: In laparoscopic HP, Adspray was easy to use for three-dimensional fields such as the pelvis and effectively prevented postoperative inflammatory adhesions. Thus, RHP may become less risky and be performed more as a minimally invasive surgery.